Pengaruh Kondisi Sosial Ekonomi Keluarga Nelayan Terhadap Pemahaman Aturan Pengelolaan Sumber Daya Laut di Sekitar Kawasan Konservasi Pulau Panjang - Santika, Lora; Asmayadi; Rafandi, Tezar (Program Studi Ilmu Kelautan, Jurusan Perikanan dan Ilmu Kelautan, Fakultas Pertanian, Universitas Mataram, 2024)
The Pulau Panjang Marine Conservation Area is among the designated conservation zones based on the Decree of the Governor of West Nusa Tenggara No. 523-505 Year 2016. Pulau Panjang boasts a diverse marine ecosystem including mangroves, seagrasses, and coral reefs, holding significant economic value, particularly in the capture fisheries sector. This study employed a survey method utilizing both primary and secondary data. The research focused on the villages of Labuhan Mapin, Labuhan Burung, Pulau Kaung, and Pulau Bungin, with the research subjects being heads of fishermen households, considering their engagement in activities within the Pulau Panjang Conservation Area. Most of the population comprises indigenous residents over 40, representing diverse ethnicities such as the Bajo, Bugis, Mandar, and Bira, among others. The fishermen community's education level is relatively low, mostly limited to primary education. Their monthly income ranges between Rp. 1,000,000 – 7,000,000, with an average monthly income of Rp. 2,957,594.00. Monthly expenses vary between Rp. 930,000 – 3,850,000 with an average of Rp. 2,273,767. The community's knowledge regarding marine resource regulations (fisheries) is reasonably good, except for the regulation prohibiting fishing in certain areas, which remains less known among the population. Overall, socio-economic factors insignificantly influence the understanding of Marine Resources within the TWP Pulau Panjang region.